Is the increased incidence of pathologically proven acute appendicitis more likely seen in elderly patients? A retrospective cohort study. (1st January 2021) - Sisik, Abdullah; Kudas, Ilyas; Basak, Fatih; Hasbahceci, Mustafa
Abstract: Aim: Although appendicitis is a disease of the young, it has been speculated that its incidence has increased among the elderly people. In this study, it was aimed to evaluate annual changes of appendicitis seen in older patients (≥60 years) throughout a 10-year period. Methods: All adult patients who were surgically treated for acute appendicitis were retrospectively analyzed with respect to pathological analysis, gender, age and proportion of the patients aged 60 or over in an annual base. Variability in the mean age and proportion of the older patients aged 60 or over throughout the study years were regarded as the main outcomes. Results: There were 3296 patients with a mean age of 30.42 ± 12 years. Distribution of gender was similar ( p = 0.636). There was a significant positive correlation in the mean age of the patients throughout the study years ( p = 0.043). Stratification by the age of 60 yielded a significant increase in percent of the older patients, from 0.93% at 2007 to 4.28% at 2016 ( p = 0.019). Conclusions: The mean age of the patients with acute appendicitis is going to increase. Therefore, it is expected that all surgeons are more likely to be confronted with elderly patients with appendicitis in the near-future.